2016
DOI: 10.12740/app/64712
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous motivation, self-efficacy, and psychophysical wellbeing in a group of Polish breastfeeding mothers- preliminary communication

Abstract: SummaryAim: The decision to quit breastfeeding is strongly influenced by feelings such as physical or psychological fatigue. Research shows that women with higher levels of breastfeeding self-efficacy are able to better cope with difficulties and continue to breastfeed for longer. The purpose of this study was to find out whether the autonomy of a mother's motivation has an effect on her breastfeeding self-efficacy. Furthermore, the study examined the relationship between breastfeeding self-efficacy and such i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A comprehensive literature review on the subject performed by de Almeida, de Araújo Barros Luz and da Veiga Ued (2015) reported that lack of training in the promotion of breastfeeding is common. Lactation specialists in Poland argue that current initiatives to boost breastfeeding practices are inadequate, and that this influences the insufficient level of knowledge about lactation among healthcare professionals ( N = 93; Kadzikowska-Wrzosek, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive literature review on the subject performed by de Almeida, de Araújo Barros Luz and da Veiga Ued (2015) reported that lack of training in the promotion of breastfeeding is common. Lactation specialists in Poland argue that current initiatives to boost breastfeeding practices are inadequate, and that this influences the insufficient level of knowledge about lactation among healthcare professionals ( N = 93; Kadzikowska-Wrzosek, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Action-oriented people, compared with state-oriented people, have further been found to display faster stress recovery and fewer adverse effects of stressors (Beckmann & Kellmann, 2004;Gröpel & Kuhl, 2009;Jaramillo & Spector, 2004). Finally, action-oriented people display better mental health than state-oriented people, both on global measures (Kadzikowska-Wrzosek, 2012;Wojdylo et al, 2014) and specific indicators like sleep quality (Kadzikowska-Wrzosek, 2018;Kroese et al, 2014), Facebook addiction (Błachnio & Przepiorka, 2016;Cudo et al, 2020), disordered eating (Blasczyk-Schiep et al, 2019), body image distortions (Kazén et al, 2019) and pain-related experiences (Buchmann et al, 2021).…”
Section: Volitional Shieldingmentioning
confidence: 99%
“…And the inability to deal efficiently with emotions is the most important factor in psychopathology. 16 Nowadays, various psychological treatments have been used to reduce anxiety, depression and pain in psychosomatic disorders, including these interventions mindfulness-based stress reduction therapy and compassion-focused therapy, which belong to the new third wave of cognitive-behavioral treatments. In a completely integrated manner, these two types of interventions control and balance physical, cognitive, and emotional functions.…”
Section: Introductionmentioning
confidence: 99%